THE EFFECT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, AND DIVIDEND POLICY ON THE VALUE OF THE COMPANY: CASE STUDY OF FOOD & BEVERAGES COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2021 PERIOD - Lulu Ramadhani; Hety Budiyanti; Nurman; Anwar Ramli; Romansyah Sahabuddin (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine managerial ownership, institutional ownership, and dividend policy on firm value in food & beverage companies listed on the IDX for the 2015-2021 period. This research is a quantitative study. The population in this research is all food & beverage companies listed on the IDX for the period 2015 – 2021. The sampling method is purposive sampling, and based on the criteria for the number of samples, there are 14 companies out of 72 companies. The data analysis technique uses descriptive analysis, multiple regression which was previously tested with classical assumptions. Based on the analysis that has been carried out, the results show that the variable managerial ownership (KM) has a positive and significant effect on firm value (Price to Book Value). Institutional ownership (IC) has a negative and insignificant effect on firm value. Dividend policy (Dividend Payout Ratio) has no positive and insignificant effect on firm value. Meanwhile, managerial ownership, institutional ownership, and dividend policy simultaneously have a positive and significant effect on firm value